2020
DOI: 10.1371/journal.pone.0234642
|View full text |Cite
|
Sign up to set email alerts
|

The role of external actors in shaping migrant health insurance in Thailand

Abstract: The role of external actors in national health policy in aid-independent countries has received relatively little attention in the literature, despite the fact that influence continues to be exerted once financial support is curtailed as countries graduate from lower income status. Focusing on a specific health policy in an aid-independent country, this qualitative study explores the role of external actors in shaping Thailand's migrant health insurance. Primary data were collected through in-depth interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…A concrete movement was the ratification of many international agreements that aim to ensure better living standards for migrants, including the 1930 Forced Labor Convention and the 2007 Work in Fishing Convention [ 31 ], and the 2017 ASEAN Declaration on the Protection and Promotion of the Rights of Migrant Workers [ 32 ]. This coincides with a study by Herbenholz which suggested that the external political force and the concern of reputational effects in foreign affairs emerged as a very powerful tool to influence the priority setting of migrant policies in Thailand [ 33 ]. Feldbaum et al underpin that health has long been intertwined with the foreign policies of states, especially in aid, trade, diplomacy, and national security [ 34 ].…”
Section: Discussionsupporting
confidence: 86%
“…A concrete movement was the ratification of many international agreements that aim to ensure better living standards for migrants, including the 1930 Forced Labor Convention and the 2007 Work in Fishing Convention [ 31 ], and the 2017 ASEAN Declaration on the Protection and Promotion of the Rights of Migrant Workers [ 32 ]. This coincides with a study by Herbenholz which suggested that the external political force and the concern of reputational effects in foreign affairs emerged as a very powerful tool to influence the priority setting of migrant policies in Thailand [ 33 ]. Feldbaum et al underpin that health has long been intertwined with the foreign policies of states, especially in aid, trade, diplomacy, and national security [ 34 ].…”
Section: Discussionsupporting
confidence: 86%
“…Similar to previous studies, we found that both migrants and their employers are reluctant to contribute to the SSS due to the perceived unaffordability of the insurance [ 10 , 20 ]. However, these structural challenges are not worsened by the SSS and HICS themselves; the driver is the underlying structural problem that excluded both schemes from the Thai UCS [ 16 , 43 ]. Integration of migrant health insurance in the Thai UCS cannot be achieved with a short-term response; it takes time to identify political feasibility through the lens of health equity and an operational system.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of the protection of migrant workers requires strict supervision and law enforcement. This supervision includes protecting Indonesian migrant workers before, during, and after work (Dewi et al, 2020;Igorevich Golubev et al, 2020). The Indonesian Migrant Worker Protection Agency (BP2MI) is a non-ministerial government agency.…”
Section: The Role Of the Indonesian Migrant Worker Protection Agency (Bp2mi)mentioning
confidence: 99%
“…The establishment of the One-Stop Integrated Service Office (LTSA) as an institution specifically tasked with providing services to the community can be said to be a breakthrough or innovation in local government management. One-Stop Services is established in local governments and focuses on districts or cities belonging to migrant workers or other considerations, such as locations on national borders (Alekseevna Fedorova et al, 2020;Herberholz, 2020;Suphanchaimat et al, 2017). The local governments must initiate the development of Indonesian society so that equitable distribution of welfare occurs not only in big cities (Rutman & Hubberstey, 2019).…”
Section: The Existence Of One-stop Integrated Service (Ltsa) In Central Javamentioning
confidence: 99%